Domestic Container Shipping Market Profile: A Case Study of Indonesia - Achmadi, Tri; Baqi, Izzuddin (Department of Naval Architecture - Diponegoro University, 2025)
Given Indonesia's status as the world's largest archipelagic nation, the shipping industry is a crucial contributor to its economy. However, the Indonesian Ship Owners Association (INSA) has reported an oversupply in the nation's commercial shipping sector. This study aimed to identify the equilibrium between supply and demand within Indonesia's container shipping market. The analysis focused on nine key container shipping liner routes and employed several methodologies, including regression, relational, supply and demand curve, market equilibrium, market structure, and voyage calculation analyses. The data for this research was sourced from Ship Arrival and Departure Report Data (LK3) and generic simulation data from business professionals. The findings indicate that the demand curve for containers is inelastic, with a value of 0.31. This suggests that cargo owners are compelled to accept the freight rates set by shipping companies. In contrast, the supply capacity curve is elastic, valued at 3.16, demonstrating that shipping companies have the flexibility to adjust their supply capacity. For instance, on the Surabaya-Makassar route, the demand and supply curves intersect at an equilibrium point of 99 million TEUs.Nm and a price of IDR 2.16 million per TEU. Conversely, on the Jakarta-Surabaya route, the demand curve does not intersect the supply curve, indicating an oversupply. To rectify this market imbalance, the supply curve would need to shift to the left, reducing the supply capacity by 258 thousand TEUs to reach equilibrium.